2022
DOI: 10.1259/bjro.20220009
|View full text |Cite
|
Sign up to set email alerts
|

Correlated MR spectroscopic imaging of breast cancer to investigate metabolites and lipids: acceleration and compressed sensing reconstruction

Abstract: Objectives: The main objective of this work was to detect novel biomarkers in breast cancer by spreading the MR spectra over two dimensions in multiple spatial locations using an accelerated 5D EP-COSI technology. Methods: The 5D EP-COSI data was non-uniformly undersampled with an acceleration factor of 8 and reconstructed using group sparsity-based compressed sensing reconstruction. Different metabolite and lipid ratios were then quantified and statistically analyzed for significance. Linear discriminant mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Ideally, the ratios should be similar on either side of the diagonal, but the lower resolution along F 1 , and t 1 ridging effects could influence these measures. Earlier studies have reported this measure from the cross peaks either above or below the diagonal or an average of the peaks on either side 16 , 32 . Statistically significant difference among IP, CT and FFT were observed in the cross peaks CP2, CP3, CP4 and CP5, especially in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ideally, the ratios should be similar on either side of the diagonal, but the lower resolution along F 1 , and t 1 ridging effects could influence these measures. Earlier studies have reported this measure from the cross peaks either above or below the diagonal or an average of the peaks on either side 16 , 32 . Statistically significant difference among IP, CT and FFT were observed in the cross peaks CP2, CP3, CP4 and CP5, especially in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 3 , 4 ). This is especially important considering the ability of 5D EP-COSI in vivo detection and quantitation of metabolites like mI and Gly, in addition to measuring lipid-based biomarkers 16 . Reports from ex vivo breast cancer tissues have also shown the role of these metabolites including mI, Gly and Cho in identifying malignancy 5 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While single-voxel spectroscopy has a reported 64–82% sensitivity and 85–91% specificity [ 41 ], the multi-voxel technique of MRSI can cover a larger area of the breast with a relatively higher spatial resolution. Advanced MRSI techniques like five-dimensional (5D) echo-planar correlated spectroscopic imaging (EP-COSI) can record two-dimensional (2D) correlated spectroscopy (COSY) from multiple regions in three-dimensional (3D) space [ 42 ]. Achieving high specificity is also challenging in MRSI due to overlapping patterns of the measures between benign and malignant lesions.…”
Section: Introductionmentioning
confidence: 99%